Pengaruh Parenting Dan Kedisiplinan Belajar Terhadap Prestasi Belajar Siswa Kelas Tinggi Sd Negeri Saripan Jepara Tahun Pelajaran 2015/2016 - RAHMAWATI, FITRI (2016)
ABSTRACT Fitri Rahmawati/A 510120055.PENGARUH PARENTING DAN KEDISIPLINAN BELAJAR TERHADAP PRESTASI BELAJAR SISWA KELAS TINGGI SD NEGERI SARIPAN JEPARA TAHUN PELAJARAN 2015/2016. Skripsi.Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Surakarta. Januari,2016. The aim of this study was to determine: (1) the influence Parenting on student achievement of high grade primary school Saripan Jepara, (2) the effect of the discipline of learning on student achievement of high grade primary school Saripan Jepara, (3) the influence Parenting and discipline to learn to student achievement Elementary School high grade Saripan Jepara. This research is descriptive quantitative research with a conclusion through statistical analysis. The population in this study are all high-grade primary school students Saripan Jepara totaling 112 students. The sample in this study amounted to 50 students. Data collection techniques used are questionnaire and documentation. The data analysis technique used is multiple linear regression analysis, ttest, Ftest, the coefficient of determination and the relative contribution and effective contribution preceded by analysis prerequisite test is a test of normality and linearity test. Based on the analysis we concluded: (1) Parenting effect on learning achievement. This is based on test results t is known that tcount> ttable is 2.283 > 2.011 and the significance value < 0.05 is 0.27. (2) The discipline of learning affect the learning achievement. This is based on test results t is known that tcount> ttable is 2.171> 2.011 and the significance value < 0.05 is 0.35 (3) Parenting and discipline to learn influence on learning achievement. This is based on Ftest known that Fcount> Ftable is 20.396 > 3.23 and a significance value < 0.05, namely 0.000. Keywords:Parenting, discipline learning, learning achievement.